Consequences of secondary nectar robbing for male components of plant reproduction. Issue 5 (24th May 2018) - Richman, Sarah K.; Irwin, Rebecca E.; Bosak, John T.; Bronstein, Judith L.
Abstract : Premise of the Study: Organisms engage in multiple species interactions simultaneously. While pollination studies generally focus on plants and pollinators exclusively, secondary robbing, a behavior that requires other species (primary robbers) to first create access holes in corollas, is common. It has been shown that secondary robbing can reduce plants' female fitness; however, we lack knowledge about its impact on male plant fitness. Methods: We experimentally simulated primary and secondary robbing in the monocarpic perennial Ipomopsis aggregata (Polemoniaceae), quantifying indirect effects on pollinator‐mediated pollen (dye) donation. We also assessed whether continual nectar removal via the floral opening has similar effects on hummingbird‐pollinator behavior as continual secondary robbing through robber holes. Key Results: We found no significant indirect effects of secondary robbing on a component of Ipomopsis male fitness. Although robbing did reduce pollen (dye) donation due to avoidance of robbed plants by pollinating hummingbirds, pollen donation did not differ between the two robbing treatments. The effects of secondary robbing on hummingbird behavior resembled effects of chronic nectar removal by pollinators. Our results indicate that hummingbird pollinators may use a combination of cues, including cues given by the presence or absence of nectar, to make foraging decisions. Conclusions: Combined with prior research, this study suggests that secondary robbing is less costly to a component of male fitness than to female fitness in Ipomopsis, broadening our knowledge of the overall costs of mutualism exploitation to total plant fitness.